2020
DOI: 10.1002/jbt.22455
|View full text |Cite
|
Sign up to set email alerts
|

MEG3 is restored by schisandrin A and represses tumor growth in choriocarcinoma cells

Abstract: Schisandrin A (SchA) has been reported as a multidrug resistance-reversing agent; however, its antitumor effects have been rarely reported. Consequently, we attempted to explore whether SchA per se possesses an antitumor property in choriocarcinoma JEG-3 and BeWo cells and its potential mechanisms. JEG-3, BeWo, and HTR-8/SVneo cells were stimulated with SchA at different concentrations (10-100 μM), and cellular viability was evaluated with Cell Counting Kit-8. After stimulation with SchA, proliferation, apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Ji and Li (2019) found that MEG3 inhibited choriocarcinoma formation by positively modulating miR-211/PI3K/AKT/AMPK signaling pathways. Similar results indicated that schisandrin A upregulated MEG3 expression and blocked the PI3K/AKT/NF-κB axis, thereby suppressing the migration and invasion of choriocarcinoma cells (Ji and Ma, 2020). Overall, these data verified that MEG3 acts as a tumor suppressor in choriocarcinoma.…”
Section: Meg3 In Choriocarcinomasupporting
confidence: 74%
See 1 more Smart Citation
“…Ji and Li (2019) found that MEG3 inhibited choriocarcinoma formation by positively modulating miR-211/PI3K/AKT/AMPK signaling pathways. Similar results indicated that schisandrin A upregulated MEG3 expression and blocked the PI3K/AKT/NF-κB axis, thereby suppressing the migration and invasion of choriocarcinoma cells (Ji and Ma, 2020). Overall, these data verified that MEG3 acts as a tumor suppressor in choriocarcinoma.…”
Section: Meg3 In Choriocarcinomasupporting
confidence: 74%
“… Zhu et al (2018) revealed that vitamin D can induce MEG3 expression, thereby inhibiting CRC cell proliferation and migration. Ji and Ma (2020) showed that schisandrin A might suppress the growth of choriocarcinoma cells by upregulating the expression of MEG3. Gao et al (2020) explained that DNMT1 can promote the proliferation of RB cells by silencing the expression of MEG3.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In choriocarcinoma cells during pregnancy, SA (10–100 μM) can reduce cell viability and proliferation activity, and inhibit migration and invasion behavior to inhibit cancer cells. In addition, SA (50 μM) also regulates the phosphorylation of the factors by inhibiting the PI3K/AKT/NF‐κB signaling cascade (Ji & Ma, 2020). This result can be achieved by increasing maternally expressed 3.…”
Section: Pharmacological Activities Of Samentioning
confidence: 99%
“…MEG3 also represses the proliferation, migration, invasion and induces apoptosis of BeWo and JEG-3 of human choriocarcinoma cells through upregulating miR-211, leading to inhibition of PI3K/AKT and AMPK pathways [ 247 ]. Moreover, a multidrug resistance-reversing agent, Schisandrin A, has been reported to repress the tumor growth in choriocarcinoma cells by upregulating MEG3 expression and downregulating PI3K/AKT/NF-κB signal cascade [ 248 ]. We summarized the detailed response of MEG3 to female-oriented cancers in Figure 8 .…”
Section: Lncrnas In Female-oriented Cancersmentioning
confidence: 99%